Les hommes de peine dans le paysage urbain - Vincent Planel (Revue des Mondes Musulmans et de la Méditerranée)
The world of day labor in Taiz has long been organized according to traditions of regional specialization. In the current context of economic crisis, the disruption of this sector induces pockets of “rural” marginality and pauperism appearing at the heart of the city, which are emblematic of the intolerable exclusions caused by modernization. Here, the presence of stereotypes of regional specialization are particularly salient concerning the urban control over a population perceived as exogenous. The analysis of informants' participation allows for reflection of a socio-historical nature: bringing to light the role played by local actors and logics, it challenges the idea of a purely macroeconomic phenomenon.